The prevalence and pattern of anaemia in diabetes and correlation of Haemoglobin with Glycated Haemoglobin - Garikapati, Amrutha; Bawankule, Shilpa; Kumar, Sunil; Lahole, Swapnil (International Journal of Psychosocial Rehabilitation, 2020)
HbA1c (glycated haemoglobin). It constitutes the HbA1 fraction of adult haemoglobin (HbA). It’s concentration depends on the life span of RBC and blood glucose levels. HbA1c is first identified as an ‘‘unusual hemoglobin among the patients with DM(diabetes) by Rahbar et al in the 1960s (1). Diabetic control was difficult before the discovery of HbA1c. After it’s discovery small studies were done comparing HbA1c to blood glucose levels, with the thought that it could be used as a measure of diabetic control. In the 1980s it came to clinical use and became a base of clinical practice (2,3). The correlation between anemia and HbA1c received limited attention. Some of the studies suggest that iron-deficiency anemia may increase concentrations of HbA1c but these studies have very limited sample size. Aged erythrocytes tend to have higher exposure to hyperglycemia, younger erythrocytes are more numerous. HbA1c level is significantly higher in iron deficiency anaemia (IDA) patients and decreased after treatment.